The Comprehensive Systematic Review of Association of Placenta Previa to the Incidence of Preeclampsia - Made Krisna Wibawa Pramartha; I Made Sudarmayasa (The International Journal of Medical Science and Health Research, 2026)
Introduction: Placenta previa and preeclampsia are major causes of maternal and perinatal morbidity worldwide. While both conditions originate from placental abnormalities, the direct association between placenta previa and preeclampsia incidence remains poorly understood. This systematic review aims to synthesize available evidence on the relationship between placenta previa and the subsequent development of preeclampsia. Methods: A comprehensive systematic review was conducted following standardized screening and data extraction protocols. We screened studies based on population (pregnant women with confirmed placenta previa), outcome (reported preeclampsia incidence), comparison groups, and study design. Eighty sources were retrieved and assessed for eligibility, with direct and indirect evidence analyzed separately. Results: The sole meta-analysis directly addressing this association (Y. Xa et al., 2015) pooled seven cohort studies and reported an overall inverse association between placenta previa and hypertensive disorders (pooled RR 0.55, 95% CI 0.32–0.97). However, this protective effect was specific to pregnancy-induced hypertension (RR 0.36, 95% CI 0.23–0.57), with no significant association for preeclampsia specifically (RR 0.94, 95% CI 0.44–2.00). Placental laterality studies demonstrated that lateral placental location strongly predicted preeclampsia (pooled OR 3.48, 95% CI 3.03–3.99), while central/fundal locations were protective against hypertension (RR 0.47, 95% CI 0.31–0.71). Endometriosis meta-analyses consistently showed strong associations with placenta previa (OR range 2.84–3.92) but only modest, inconsistent links with preeclampsia. Discussion: The available evidence suggests that placenta previa is not significantly associated with preeclampsia incidence. The apparent protective effect against hypertensive disorders is attributable to reduced gestational hypertension risk rather than preeclampsia. Distinct pathophysiological mechanisms may underlie different placental location abnormalities: lateral implantation may compromise uterine artery perfusion leading to preeclampsia, while low-lying implantation in placenta previa does not involve the same laterality-dependent hemodynamic deficit. Conclusion: Current evidence does not support an association between placenta previa and increased preeclampsia risk. Future research should distinguish between hypertensive disorder subtypes and employ standardized definitions to clarify these relationships.